Far From Home: Reading and Word Study - Pickett, William P. (Boston Heinle and Heinle Publishers, 1994)
Far From Home is a reading text that emphasizes word study. This book helps students acquire a basic vocabulary that will make them better readers and it accomplishes this end through the presentation of reading as well as other exercises designed to foster the development of a host of language, thinking, and study skills.
Keywords: Reading